The Performance of Cihateup Ducks Liver Given Natural Isotonic in Dry Maintenance Systems - Nurul Frasiska; Putri Dian Wulansari; Novia Rahayu (Universitas Tidar, 2019)
This study aims to observe the condition of serum glutamate pyruvate transaminase and serum oxaloacetate transaminase as an illustration of the liver performance of Cihateup Ducks that were given natural isotonic through drinking water in a dry maintenance system. The animals used were Cihateup ducks, kept for 8 weeks with 48 animals and divided into four treatments, namely T0 (Control with drinking water without isotonic), T1 (7% sugar + 2% lime juice + 25 mg celery extract + 0.8 salt g), T2 (7% sugar + 3% lime juice + 50 mg celery extract + 0.9 g salt), T3 (7% sugar + 4% lime juice + 75 mg celery extract + 1 g salt). Each treatment was repeated 4 times, 3 ducks for one treatment plot. This study used a Completely Randomized Design (CRD). Data were tested using analysis of variance and continued with Duncan's further test at 5% level. The results showed that the treatment of T2 (7% Sugar + 3% Lime juice + celery extract 50 mg + 0.9 g salt) significantly produced the lowest SGPT levels and seen a tendency for SGOT to decrease but not significantly. The use of natural isotonic solutions can be given to Cihateup ducks on dry system maintenance.Keywords: Cihateup’s duck, Dry system, Natural isotonic, SGOT, SGPT